Meningkatkan Kemampuan Berhitung Melalui Media Kartu Angka Interaktif Pada Kelompok Usia 5-6 Tahun Taman Kanak – Kanak Taman Hijau, Kota Batam - Diana Indah Palupi; Diana Earlyana Lesmana; Dian Farista; Emma Rahmani; Erlin Yusnita; Agus Sudarya (Jurnal Pendidikan Indonesia, 2022)
Children begin to enter the preschool period in the age range of 5-6 years, this age is a period of preparation to enter formal education actually in elementary school. Cognitive development is one aspect of development that must always be given stimulation. The ability to count is part of the aspect of cognitive development. The purpose of this study in general is "Improving the ability to count through the medium of interactive number cards in the age group of 5-6 Taman Kanak – Kanak Taman Hijau, Batam City". To determine the achievement of children in the learning development activities carried out, an assessment is carried out by means of Class Action Research through the medium of interactive number cards. This study uses Class Action Research of Kemmis and Mc Taggrat cycle models with four stages, namely: planning, implementation, observation and reflection. The data of this study comes from the results of action observations and evaluation results. The study was conducted in two cycles. Each cycle is based on the stages of activity planning, execution of actions , observation and post-analysis reflection. Before the step of cycle 1, 4 students were able to do numeracy activities with worksheet media. After cycle 1 there was the addition of 3 more children who showed better counting skills. By the end of the 2nd cycle, 11 children were able to develop very well and 2 children developed as expected. This shows that the use of interactive number card media has a positive impact and can improve students' ability to do numeracy.Meningkatkan kemampuan berhitung